Somatostatin receptor scintigraphy in patients with cat-scratch disease - Krause, R.; Piswanger-Soelkner, C.; Lipp, R. W.; Daxböck, F.; Schnedl, W. J.; Hoier, S.; Reisinger, E. C. (Nuklearmedizin - NuclearMedicine, 2006)
Aim: Somatostatin receptor scintigraphy images various neoplastic, granulomatous, and auto-immun diseases. Cat-scratch disease in an infectious granulomatous disease usually affecting the lymphnodes. It is not known whether cat-scratch disease provides positive somatostatin receptor scintigrams. Patients, methods: Twelve patients with lymphadenitis and suspected cat-scratch disease were investigated by immunofluorescence antibody testing and somatostatin receptor scintigraphy. Suppurated lymphnodes were extracted or drained and Bartonella henselae specific PCR was then performed. Results: Eleven of 12 patients showed IgG antibodies against B. henselea. SRS showed positive scintigraphic results in 6 of 11 patients with CSD. B. henselae DNA was detected in tissue of lymphnodes from 4 of 5 patients with lymphnode extraction or lymphnode drainage. SRS demonstrated positive scintigrams in all patients with a positive PCR. In one patient with suspected CSD SRS was negative as well as antibody testing. Conclusion: Somatostatin receptor scintigraphy correlated with positive Bartonella henselae specific PCR tests and positive Bartonella henselae specific antibody tests in patients with CSD.
Keywords: Cat-scratch disease; somatostatin receptor scintigraphy